HUBUNGAN TINGKAT SPIRITUALITAS DENGAN KECEMASAN PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISIS - Widyasari, Putu Rossi; Manangkot, Meril Valentine; Juniartha, I Gusti Ngurah (Coping: Community of Publishing in Nursing; Vol 11 No 4 (2023): Agustus 2023DO - 10.24843/coping.2023.v11.i04.p14, 2023)
Chronic kidney disease (CKD) is a state of decreased kidney function. One of the therapeutic options for patients with chronic kidney disease is hemodialysis. Patients undergoing hemodialysis therapy can experience anxiety, anxiety will have an impact on the process of hemodialysis. One of the efforts to cope with anxiety, especially in patients with chronic diseases is to improve the aspects of spirituality. This study aims to determine the relationship of level of spirituality with anxiety in patients with chronic renal disease undergoing hemodialysis therapy. This research was conducted on April 10-May 10, 2021. This research is quantitative research with cross sectional design. In this study followed by 50 respondents. The results showed that the level of spirituality of the high patient as many as 29 people (58%) and the majority of patients undergoing hemodialysis therapy have higher levels of anxiety mild that as many as 33 people (66%). The relationship of level of spirituality and anxiety in patients with chronic renal disease undergoing hemodialysis therapy were analyzed using the test of Spearman. The test results show there is a relationship between the level of spirituality with anxiety in patients with chronic renal failure undergoing hemodialysis therapy (p value = 0,000; r = -0,617). It can be concluded that the higher the level of spirituality of the patient then the mild level of anxiety of patients undergoing hemodialysis therapy. Expected to respondents can maintain a good level of anxiety and level of spirituality.